Entropy tailoring of thermodynamic behaviors and magnetocaloric effects in (GdTbDy)CoAl metallic glasses - Fan Jin; Chenchen Yuan; Changmeng Pang; Xinming Wang; Chengrong Cao; Juntao Huo (Materials & Design, 2024)
The effect of configuration entropy (ΔSconf) on thermal properties and magnetocaloric effects (MCE) of metallic glasses (MGs) remains vague. In this work, Tb55Co17.5Al27.5 low-, (Gd0.5Tb0.5)55Co17.5Al27.5 medium-, and (Gd1/3Tb1/3Dy1/3)55Co17.5Al27.5 high-entropy (LE, ME, and HE) MGs with critical diameters more than 5 mm were successfully fabricated. Systematic investigations into their thermodynamic behaviors suggest that high ΔSconf might deteriorate glass forming ability (GFA) along with reduced viscosity. Simultaneously, an improved thermal stability was observed in ME and HE MGs for their high activation energies for glass transition, crystal nucleation and growth, while the notable ordered structure in HE MG could accelerate glass transition and crystal growth by reducing activation energies. Studies of MCE indicate that the distinguished spin glass behaviors and higher structural order in HE MGs comprehensively contribute to an enhanced relative cooling power and a broader magnetic-transition temperature range, whereas the change of Curie temperature and maximum magnetic entropy more depends on the de Gennes factor rather than ΔSconf. All three designed MGs manifesting the competitive GFA and MCE could be candidates for magnetic refrigeration. Our studies show that entropy tailoring seems to play a dominant role in determining thermodynamic behaviors, which could help to design more stable MCE MGs.